Genomics-guided discovery of a new and significantly better source of anticancer natural drug FK228 - Xiangyang Liu; Feng Xie; Leah B. Doughty; Qi Wang; Lixin Zhang; Xueting Liu; Yi-Qiang Cheng (Synthetic and Systems Biotechnology, 2018)
FK228 is an FDA-approved anticancer drug naturally produced by Chromobacterium violaceum No. 968 up to 19 mg/L in a pilot industry-scale batch fermentation. Here we report a genomics-guided discovery of Burkholderia thailandensis MSMB43 as a new and significantly better source of FK228. The genome of B. thailandensis MSMB43 was found to contain a functional biosynthetic gene cluster highly homologous to that of FK228 in C. violaceum No. 968, and the bacterium indeed produces authentic FK228. By simple fermentation in shaking flasks in a preferred M8 medium, B. thailandensis MSMB43 produced FK228 up to 67.7 mg/L; by fed-batch fermentation in a 20-L fermentor in M8 medium, B. thailandensis MSMB43 produced FK228 up to 115.9 mg/L, which is 95 fold higher than that of C. violaceum No. 968 under the same laboratory fermentation conditions. RT-PCR analysis indicated that the high FK228 yield of B. thailandensis MSMB43 was due to high expression of biosynthetic genes, represented by Bth_depA, during the fermentation process. Further genetic manipulation resulted in a recombinant strain, B. thailandensis MSMB43/pBMTL3-tdpR, which harbors a broad host-range vector expressing the thailandepsin biosynthetic pathway regulatory gene tdpR. This engineered strain produced up to 168.5 mg/L of FK228 in fed-batch fermentation in a 20-L fermentor in M8 medium. Therefore, the wild-type B. thailandensis MSMB43 or its engineered derivative could potentially be a good starting point for an industrial process to improve FK228 production for its expanding use in therapy. Keywords: Burkholderia thailandensis MSMB43, Fermentation optimization, FK228, Genome mining, Natural product, Productivity